Tracer studies in the rat demonstrate misdirected filtration and peritubular filtrate spreading in nephrons with segmental glomerulosclerosis - Kriz, Wilhelm; Hartmann, Ingrid; Hosser, Hiltraud; Hähnel, Brunhilde; Kränzlin, Bettina; Provoost, Abaraham P.; Gretz, Norbert (Journal of the American Society of Nephrology, 2001)
Abstract: In two genetic models of “classic” focal segmental glomerulosclerosis (FSGS), the Milan normotensive and the Fawn-hooded hypertensive rats, tracer studies were performed to test the hypothesis that misdirected glomerular filtration and peritubular filtrate spreading are relevant mechanisms that contribute to nephron degeneration in this disease. Two exogenous tracers, lissamine green and horse spleen ferritin, were administered by intravenous injection and subsequently traced histologically in serial kidney sections. In contrast to control rats, both tracers in kidneys of Milan normotensive and Fawn-hooded hypertensive rats with established FSGS were found to accumulate extracellularly at the following sites: within tuft adhesions to Bowman9s capsule and associated paraglomerular spaces, at the glomerulotubular junction contained within extensions of the paraglomerular spaces onto the tubule, and within subepithelial peritubular spaces eventually encircling the entire proximal convolution of an affected nephron. This distribution strongly suggests the existence of misdirected filtration into tuft adhesions to Bowman9s capsule and subsequent spreading of the filtrate around the entire circumference of a glomerulus and, alongside the glomerulotubular junction, onto the outer aspect of the corresponding tubule. This leads to an interstitial response that consists of the formation of a barrier of sheet-like fibroblast processes around the affected nephron, which confines the filtrate spreading and, subsequently, the destructive process to the affected nephron. No evidence was found that either misdirected filtration and peritubular filtrate spreading themselves or the associated tubulo-interstitial process led to the transfer of the injury from an affected nephron to an unaffected nephron. It is concluded that in the context of FSGS development, misdirected filtration and peritubular filtrate spreading are important damaging mechanisms that underlie the extension of glomerular injury to the corresponding tubulointerstitium, thus leading finally to degeneration of both the glomerulus and the tubule of a severely injured nephron.